A Plan for Librarian's Adaptation to Changing Information Environment - Gopinath, M. A. (Journal of Information and Knowledge, 2014)
Discusses the impact of information technology on changing information environment in the society. identifies the role of information professionals as to provide access to information. The basic infrastructure to be developed for this purpose cans for a variety of knowledge and skill. Provides a madule for a course in Information Technology for the information professionals.